PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PD. BPR BANK KLATEN DENGAN KOMITMEN ORGANISASI SEBAGAI INTERVENING - Purwito Kesdu AC (AKTUAL, 2014)
The purpose of this study is to determine the influence of leadership and motivation on employees performance at PD. BPR Bank Klaten with an organizational commitment as an intervening variable. The result shows that : there is the influence of leadership, motivation, and organizational commitment as a variable intervening on employees performance at PD BPR Bank Klaten. This study is a survey to PD. BPR Bank employees Klaten with 70 employees as the sample . Data have been collected by questionnaires processed by a linier regression, path analysis, t test, F test and test R2. T tests shows that there is an influence of leadership, motivation, and organizational commitment to employees performance at PD BPR Bank Klaten. The F tests has shown that there is an influence of leadership, motivation, and organizational commitment to employees performance at PD. BPR Bank Klaten simultaneously. Keyword: leadership, motivation, organization commitment and performance.